Subjective socioeconomic status and health in cross-national comparison. (January 2016) - Präg, Patrick; Mills, Melinda C.; Wittek, Rafael
Abstract: Research has established a robust association between subjective socioeconomic status (SES) and health outcomes, which holds over and above the associations between objective markers of SES and health. Furthermore, comparative research on health inequalities has shown considerable variation in the relationship between different objective markers of SES and health across countries. Drawing on data from 29 countries, we present the first cross-national study on the subjective SES–health relationship. For two health outcomes, namely self-rated health (SRH) and psychological wellbeing, we are able to confirm that subjective SES is related to health in all countries under study, even when income, education, and occupational prestige are accounted for. Furthermore, we document considerable variation in the strength of the subjective SES–health association across countries. This variation however is largely independent of country differences in income inequality and country affluence. The health benefits of a high subjective SES appear to be slightly larger in more affluent countries, but only for SRH, not for psychological wellbeing. Highlights: First cross-national study on subjective socioeconomic status (SES) and health. Subjective SES and health are associated in all countries. Subjective SES–health association holds even when controlling for objective SES. Size of the subjective SES–health gradient not affected by income inequality.